NILAI EKONOMI SAMPAH ANORGANIK YANG DI REDUKSI PEMULUNG DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI TEMPAT PEMBUANGAN AKHIR (TPA) BASIRIH KOTA BANJARMASIN - Endah S. Qomariah; Emy Rahmawati; Abdurrahman Abdurrahman; Setia Budi Peran (EnviroScienteae, 2011)
Inorganic waste has economic value because it can be recycled. The presences of inorganic scavengers collect waste discharge to contribute to the reduction of waste and reduce environmental damage. This study aims to obtain economic value calculation inorganic waste that goes into landfill and has been reduced by scavengers, knowing the factors that influence the rate reduction by scavengers, and to get a view of the role of the scavengers and the collectors or the container in reducing waste in landfill Basirih Banjarmasin and the description of the relationship between the working procedures of the scavengers and collectors. Research conducted at the place of final disposal (landfill) waste in the area Basirih Banjarmasin in South Kalimantan Province. Method of survey conducted through interviews and questionnaires with a sample of respondents 60 people scavengers drawn at random, while for levels of collectors (containers) carried out the census. The calculation result shows that the economic value of waste is reduced inorganic waste in 2008 amounted to Rp.423.655.500, - with an average amount of waste that is reduced 960 tons / year, in the year 2009 amounting to Rp. 501 966 250, - with the amount of waste reduction on average 1300 tonnes / year, and in 2010 was Rp 585,952,750, - with a reduction of 1551 tons / year. Factors affecting the economic value of waste are age, length of time the scavengers work in one day and length of experience scavenged. Scavenging activity has indirectly reduced the amount of waste volume and load capability of the environment.